EKOWISATA MANGROVE DI MEMPAWAH - Surya Priva Jaya; Lestari Lestari; Valentinus Pebriano (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Mempawah Regency has natural tourism potential in the form of mangrove forests which are ideal in optimizing the function of tourism areas related to conservation, education and communal recreation spaces. The potential tourism object for development in Mempawah Regency is the mangrove forest. The development of mangrove forest tourism has received minimal attention from the Government. It is indicated by the non-ideal facilities and functional buildings in mangrove forest tourism. Mangrove forest tourism contains mangrove forests that are beautiful and natural but have suffered damage to the natural environment, less than ideal and optimal infrastructure. Ecotourism is a solution and form of optimizing mangrove forests in Mempawah, tourism, and nature conservation on the coast. The purpose of this paper is to design a mangrove ecotourism area that is recreational, educative, and conservative. Consideration of ocean landscapes and mangrove forest landscapes on land as the main value in developing the attractiveness of the area and its buildings. The planning site is on Jalan Gusti Sulung Lelanang, Pasir Village, Mempawah Hilir District, Mempawah Regency which has a planning area of 2.95 Ha. The approach and concept used in the planning of mangrove ecotourism is an ecological architectural approach with consideration of the site, actors and activities, the amount of space, architectural aesthetic elements, structures, utilities. The design methodology applied is the Zeisel imaging method of the surrounding ecology. The result of the design of mangrove ecotourism is a recreational, educative, conservative mangrove forest natural tourism area in Mempawah Regency.